Business as unusual : my entrepreneurial journey, profits with principles. - Roddick, Anita, 1942-2007; Roddick, Anita, 1942-2007 (West Sussex : Anita Roddick Books, 2008)
Flaunting a title like Business as Unusual, Anita Roddick's company biography is anything but your run-of-the-mill book on how to create, nurture, and run a successful company. While it does give a firsthand account of the birth of The Body Shop and Roddick's own particular leadership style of creative (and sometimes chaotic) passion, it doubles as a clarion call for business to tackle the big issues of life alongside the pursuit of profits, with heart, soul and conscience. Roddick grew up in a large Italian immigrant family in small town in blue-collar England, where she was instilled with an intense work ethic and an irreverent, entrepreneurial spirit. Though she admits to having opened her first Body Shop as a way to make ends meet, Roddick developed the company around her zealous belief that, since there is "no more powerful institution in society than business ... it is more important than ever before for business to assume a moral leadership in society." Her concern for protecting
The environment and indigenous people's cultures, and of seeing all of life as interconnected, have directed the growth of the company and inspired much of this book. Her account moves from an initial description of what she sees as the problem with "business as usual," through a history of The Body Shop as illustrating her philosophies on fostering passionate activism, building community, making it as a woman, and succeeding in business. Though Roddick's tone occasionally lapses into what might be interpreted as a rather self-righteous one (particularly in her references to most of the company's competition as merely "imitation"), it is driven by a feisty belief in her ideals. The chapter that describes The Body Shop launch into the U.S. market and its subsequent problems with intense competition is not exactly an American love-fest, but for those readers on this side of the Atlantic who don't take themselves too seriously, it's an informative and often amusing take on the trials of cross-cultural
Marketing. While praise of The Body Shop's good deeds to date is woven into much of what she discusses, Roddick is not afraid of being honest. Indeed, she presents some of the company's less flattering underbelly, such as a failed experiment in trading directly with an indigenous tribe and the unsuccessful "reorganization" of the company by an unresearched external consultant, which is far more daring than most business leaders are in discussing their corporate offspring. The book would have benefited from a more detailed and less defensive presentation of the media storm that surrounded the company from 1992 to 1994 (which comes dangerously close to being a diatribe), but Roddick's conversational writing style--extremely effective in relaying fervent dedication--doesn't leave room for a lot of legal analysis.
Keywords: Ethisch ondernemen; The Body Shop; Vrouwen en zakenleven